Assessment of Knowledge on Disaster Preparedness among Adult in a Selected Rural Community at Kanchipuram District Tamil Nadu, India (Medico Legal Update, 2020)
“Assessment of knowledge on Disaster preparedness among Adults’’. The objectives of this study areto assess the level of knowledge on disaster preparedness among adults and associate the knowledge ondisaster preparedness among adults with selected demographic variables. The sampling technique used wassimple random sampling technique with the samples of 100 adults. The study assessed the knowledge ondisaster preparedness among adults. The data collection tool was validated by nursing experts. The collecteddata was tabulated and analyzed. That based on the age of adults 69(69%) of adults were in between 20-40years, 26(26%) were in between 41-59 years, 5(5%) were above 60 years. According to the sex distribution52(52%) were male and 48(48%) were female. According to the educational status 72(72%) were studiedup to primary and middle school, 23(23%) were studied upto secondary and higher secondary educationschool and 5(5%) were under graduate. Regarding the type of disaster 68 were experienced flood, 72 wereexperienced cyclone, 20 were experienced earthquake and 1 were experienced draught . Regarding thesources of knowledge subjects gained knowledge from newspaper 16(16.4%), from television 82(84.4%),from phone 3(3.09%), from Panchayat 1(1.03%) and from pamphlet 1(1.03%). Regarding previous disasterstatus 42(42%) were experienced disaster once, 36(36%) were experienced disaster twice and 22(22%) wereexperienced disaster more than thrice . To create the awareness among public and to reduce the Impact ofdisaster.